MERCURY-INDUCED NEUROBEHAVIORAL DEFICIT AND ITS AMELIORATING EFFECTS OF AQUEOUS EXTRACT OF TRAPA BISPINOSA - Phukan, Pankaj; Namasudra, Sanjit; Bawari, Meenakshi; Sengupta, Mahuya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to evaluate the effects of aqueous extract of dry fruits of Trapa bispinosa (TB) in alleviating mercury (Hg)-induced neurobehavioral toxicity. Methods: A total of 36 adult male Swiss albino mice weighing 25–30 g were equally divided into six groups, namely I–VI. Group I received distilled water, Group II received mercuric chloride (1.5 mg/kg), Group III received TB extract low dose (150 mg/kg), Group IV received TB extract high dose (300 mg/kg), Group V received mercuric chloride plus TB extract low dose, and Group VI received mercuric chloride plus TB extract high dose. All the groups received doses orally through oral gavage tube and the treatment lasted for 14 days. The behavioral effects were evaluated with locomotor activity in the open field test (OFT), spatial learning ability and memory in the Morris water maze test (MWM), immobility in Forced swimming test (FST) and anxiety in Elevated plus maze test (EPM). Result: In the present study, it was observed that Hg-exposed mice significantly decreased the locomotor activity (p<0.001), time spent in open arms (p<0.001), number of open arm entries (p<0.01), number of annulus crossovers (p<0.001) and increased immobility (p<0.001), escape latency (p<0.01), and path length (p<0.001) in mice. The aqueous extract of TB significantly reduced the neurotoxic effects of Hg. The aqueous extract of TB showed to increase the locomotor activity (p<0.01), time spent in open arms (p<0.01), number of open arm entries (p<0.05), and number of annulus crossovers (p<0.001), which was decreased in Hg-exposed mice. TB extract also showed to decrease the immobility (p<0.001), escape latency (p<0.05), and path length (p<0.001) in Hg-fed mice. Conclusion: On the basis of the results obtained from the behavioral study, the present study indicates that mercuric chloride caused neurobehavioral changes which were significantly reversed by the aqueous extract of TB. Thus, TB was found to be effective in ameliorating the neurobehavioral deficit induced by Hg exposure.